ANALISIS EFESIENSI TRAFO DAYA TERHADAP PENGOPERASIAN BEBERAPA JENIS HARMONIC FILTER - Maharta Pemayun, A.A Gede; Budiastra, I Nym; Rinas, I W (Jurnal SPEKTRUM; Vol 7 No 4 (2020): Jurnal SPEKTRUM, 2020)
Nonlinear load is one of the causes of harmonics in utility systems. To reduce harmonic distortion that appears, usually in utility systems, Harmonic Filters are operated such as: passive filters, active filters, series hybrid filters and hybrid shunt filters. Harmonic distortion that occurs will increase losses in the utility system. Losses that appear will affect the efficiency of the Power transformer being operated. From the analysis results, the order of the best to worst filter efficiency is hybride filter (? = 97.26%), active filter (? = 96.72%) and passive filter (? = 95.73%).